Alpha-Thalassaemia in Sardinian infants. Issue 5 (October 1980) - Galanello, R; Diana, G; Furbetta, M; Angius, A; Melis, M A; Rosatelli, C; Cao, A
Abstract : A haemoglobin survey carried out in southern Sardinian newborn infants showed an overall incidence of 12.9% with haemoglobin Bart's of more than 1%. The distribution was trimodal: low (1 to 2%), intermediate (2 to 10%), and high (about 25%). A considerable overlap was seen between the first two groups. Both the 1 to 2% and 2 to 10% groups had thalassaemia-like red cell indices at birth. Newborn infants ascertained as having alpha-thalassaemia at follow-up did not necessarily have unbalanced alpha/non-alpha chain synthesis at birth. At follow-up examination two subjects in the 25% group had developed haemoglobin H disease, and the 2 to 10% group had thalassaemia-like red cell indices and unbalanced globin chain synthesis ratios indicative of heterozygous alpha-thalassaemia. The 1 to 2% group either had normal or slightly reduced alpha-chain synthesis ratios, indicative of the silent alpha-thalassaemia carrier state. Two subjects with 2.0% and 2.5% haemoglobin Bart's at birth had heterozygous beta-thalassaemia at follow-up. Therefore, they were double heterozygotes for alpha- and beta-thalassaemia with alpha/beta-globin chain synthesis ratios of 0.81 and 0.86. Genotype assessment in a few families showed that infants with haemoglobin Bart's levels of more than 2% may have one of the genotypes –alpha/ –alpha or – –/alpha alpha.